Comprehensive Analysis of Mahasarakham University’s Sustainability Efforts and Global Ranking Achievements in 2024 - Srivilai, Prayook; Khotdee, Mathinee; Kaewplang, Siwa; Thuangchon, Sattawat; Chaitongrat, Tanayut; Sivanpheng, Ounla; Kangrang, Anongrit (Journal of Ecohumanism, 2025)
Universities play a pivotal role in advancing global sustainability through education, impactful research, and environmentally responsible operations. This study evaluates the sustainability initiatives of Mahasarakham University (MSU) in alignment with the UI Green Metric World University Rankings criteria, with a particular focus on its performance in 2024. Since joining the rankings in 2011 with an initial total score of 4,781 points, MSU has steadily improved, achieving a total score of 8,475 points in 2024. The analysis examines three primary dimensions: the integration of sustainability into academic curricula, where sustainable courses increased to 55 programs out of 95 total offerings; the enhancement of sustainability-focused research, reflected in a 77% increase in related publications over the past three years; and the implementation of community engagement projects, which rose significantly from 44 projects in 2021 to 71 in 2023. The findings demonstrate MSU’s consistent progress, with notable achievements in aligning its strategic plans with sustainability goals. However, challenges remain in optimizing resource allocation and expanding international collaborations. By synthesizing lessons learned and analyzing trends, this study identifies best practices and offers strategic recommendations for MSU and other institutions aspiring to excel in global sustainability benchmarks. The results underscore universities’ essential role as catalysts for sustainable development, providing actionable insights into enhancing operational efficiency and academic contributions.